Effects of Switching Frequency Modulation on Input Power Quality of Boost Power Factor Correction Converter - Deniss Stepins; Jin Huang (Institute of Advanced Engineering and Science, 2017)
Switching frequency modulation (SFM) as spread-spectrum technique has been used for electromagnetic interference reduction in switching power converters. In this paper, a switching-frequency-modulated boost power factor correction (PFC) converter operating in continuous conduction mode is analysed in detail in terms of its input power quality. Initially, the effect of SFM on the input current total harmonic distortion, power factor and low-frequency harmonics of the PFC converter are studied by using computer simulations. Some advices on choosing parameters of SFM are given. Then the theoretical results are verified experimentally. It is shown that, from a power quality point of view, SFM can be harmful (it can significantly worsen the power quality of the PFC converter) or almost harmless. The results depend on how properly the modulation parameters are selected.